Al-Dhara'i and Maqasid al-Shariah: a case study of Islamic insurance - Abdul Aziz, Akhtarzaitie (IIUM Press, 2010)
This paper aims at exploring the concept of al-dhara'i in its broad meaning, both at the preventive and proactive levels (sadd and fath aldhara'i). The application of al-dhara'i at both levels plays a significant role as a practical mechanism towards the realisation of maqasid, due to the cause effect relationship between means and objectives. Thus, the legality or the Shariah value of an act could be determined based on its possible results in procuring benefits and/or preventing harm. Islamic Insurance has been considered a new development in fiqh al-muamalat. The current debate is not on the question of legality of insurance as a concept and practice but rather to provide an Islamic model of insurance that conforms to the criteria of the Shariah that helps realise its objectives. Due to the unavailability of direct texts on this issue, some practical aspects of insurance depend largely upon the predominance of either beneficial or evil ends. This paper will, therefore, look into some controversial issues prevailing in insurance practice and an attempt will be made to review the issues within the framework of realisation of Maqasid al-Shariah via the application of dhara'i both at preventive and proactive levels.